SISTEM INFORMASI PENGOLAHAN DATA AKUNTANSI PERUSAHAAN MENGGUNAKAN ZAHIR ACCOUNTING VERSI 5.1 - Tyas, Anindya Ikaning; Ela Revita, Maria Lapriska Dian; Ariyati, Indah (Fundamental Management Journal, 2019)
Technological developments have been used to support the company's performance in various fields. Company data processing related to cash outlays and cash income on CV. Green Iroha Bekasi which is still manually applied using accounting software, namely Zahir Accounting Version 5.1. Processing using Zahir Accounitng version 5.1 aims to ensure that all financial data in the company are not overlooked starting from estimates, recording, accounting to reports so that the company can find out the company's financial position in a certain period of time. Computerized financial data storage becomes safe and organized systematically and minimizes errors so as to facilitate decision making. Keyword : information system, accounting data, zahir accounting